PATTERNS OF PUBLIC SPACES BASED ON ‘SPORT FOR ALL’ AND PEOPLE’S ADAPTATION PROCESS IN SEMARANG CITY - Priyono, Bambang; Rohidi, Tjetjep Rohendi; Soesilowati, Etty (Universitas Negeri Semarang, 2017)
As part of the culture, sport has a variety of forms and meaning that undergo changes from time to time and from society to society. This study is intended to describe the accessability of public spaces, the adaptation patterns of the use of public spaces by participants of â€˜sport for allâ€™, forms of interaction, communication and image of â€œsport for allâ€, and sociocultural factors that support â€œsport for allâ€ within the car free day program in Simpang Lima Complex. A phenomenologic naturalistic approach by using a multi-site design was used. The subjects consisted of heads of Semarang City Services, and users of car free day activities. The data were collected by using observation, documents, and interviews.The results show that first, public spaces are external and accessible by all people and consist of parks, city square, roads, and sidewalks. Second, the users of â€œsport for allâ€ adapt to the available spaces through car free day activities. Third, the symbols of interaction, communication and image of â€œsport for allâ€ are similar including accessories, fashion and identities to visually demonstrate their community or group existence. Fourth, physical, social, ecologic, and economic aspects of the sociocultural factors support â€œsport for allâ€.